Reconciling Institutional and Professional Requirements in the Specialised Inverse Translation Class – A Case Study - Rodríguez-Inés, Patricia; Fox, Olivia (Meta, 2018)
Translating into a language that is not one’s native language is no easy task, but one which may be necessary in certain settings. If a market niche exists for professional translators whose working language is not their native language, as studies have shown it does in Spain, it seems appropriate that translation trainees should be encouraged to develop their competence in what is generally known in Translation Studies as inverse (A-B/C) translation, in order to satisfy market requirements. Given current European Higher Education Area (EHEA) requirements for training students for the professional workplace, most translation degree programs in universities in Spain include subjects in which students are required to translate into the foreign language. This paper describes an early attempt to reconcile institutional requirements (curriculum design, assessment, reporting) and professional requirements (development of translation and instrumental competences, together with so-called softskills) in the specialised inverse translation class in the Faculty of Translation and Interpreting of the Universitat Autònoma de Barcelona. A competence-based, learner-centred, process-oriented curriculum was instituted.